Comparative Analysis and Harmonization of Global Halal Standards - Lutfika, Evrin; Kusnandar, Feri; Hunaefi, Dase (International Journal of Halal Research, 2022)
Muslim awareness of halal lifestyles has developed into a lucrative business opportunity on global scale. Currently, there is no globally recognized halal standard as a reference for the establishment of a global halal system. The absence of global halal standard restricts the growth of halal industries. The purpose of this study was to identify and compare the halal standards applied in some countries as well as to propose a global halal standard for harmonization. A comparative analysis methodology was applied by conducting an in-depth review on five halal standards frequently used as references in some countries (OIC/SMIIC 1: 2011, UAE.S/GSO 2055-1:2015, MS 1500:2009, MUIS-HC-S001, HAS 23000). The review focused in aspects that directly affects to the halal status of food products (materials, processing facilities, and products). There are similarities, differences and incompleteness in five halal standards in terms of material, product and facility aspect. The same standard can be directly adopted as a proposed global halal standard, whereas for those differed and incomplete standards, depth analysis was conducted and new clauses are proposed. There are 24 clauses that are harmonized in proposed global standard, while five clauses require further discussion among Islamic scholars. SMIIC is being considered as a center for the harmonization of international halal standard.